On the feasibility of full-duplex relaying in the presence of loop interference - Riihonen, Taneli; Werner, Stefan; Wichman, Risto; Zacarias, Eduardo B. (2009 IEEE 10th Workshop on Signal Processing Advances in Wireless Communications, 2009)
We consider a two-hop infrastructure-based relay link with three transmit power allocation methods. Both amplify-and-forward and decode-and-forward protocols are studied. Fundamentally, a relay can operate either in a full-duplex or in a half-duplex mode. The performance in full-duplex relaying is degraded due to loop interference from the relay output to the relay input. On the other hand, the half-duplex mode eliminates the loop interference, but this reduces the end-to-end rate. In this paper, we study the feasibility of the full-duplex mode in terms of end-to-end capacity. In particular, we evaluate break-even loop interference levels, below which the full-duplex mode outperforms the half-duplex mode. The analysis shows that the full-duplex mode is feasible in the presence of reasonably high loop interference power and can offer higher capacity than the half-duplex mode.